2017
DOI: 10.21827/5a6af9c46c2ff
|View full text |Cite
|
Sign up to set email alerts
|

The Colonial Aspects of International Environmental Law: Treaties as Promoters of Continuous Structural Violence

Abstract: The formation of international institutions in the twentieth century occurs under a scenario marked by the rule of colonialism and imperialism. Thus, instead of reducing inequalities in the world system, international institutions reproduce a prevalent logic of material and subjective discrimination based on a colonialist ideology marked by violence, which is communicated in a certain way so that it can justify its importance and legitimacy. The colonial violence is perpetuated under the form of symbolic viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In a time when academics, pundits, and politicians are talking about the need for derisking and de-escalating in international relations, it seems that Cassidy (2023) wants to add more gasoline to the fire. In addition, this argument reflects a persistent colonial legacy that influences the climate change narrative and the policies that have resulted from it, which are directed at developing countries, thus resulting in the enduring injustices that occasionally put the industrial aspirations of the Global North against the existence of the Global South, the most vulnerable to the effects of developed countries (Hickel, 2021;Castro, 2017).…”
Section: The Foreign Pollution Fee: Protectionism Disguised In Enviro...mentioning
confidence: 99%
“…In a time when academics, pundits, and politicians are talking about the need for derisking and de-escalating in international relations, it seems that Cassidy (2023) wants to add more gasoline to the fire. In addition, this argument reflects a persistent colonial legacy that influences the climate change narrative and the policies that have resulted from it, which are directed at developing countries, thus resulting in the enduring injustices that occasionally put the industrial aspirations of the Global North against the existence of the Global South, the most vulnerable to the effects of developed countries (Hickel, 2021;Castro, 2017).…”
Section: The Foreign Pollution Fee: Protectionism Disguised In Enviro...mentioning
confidence: 99%
“…Bullard's study in 2007, found that race was more likely to predispose a population to environmental pollution than socioeconomic status. 29 In the case of Africa, the perception of the region, its people and its relevance, in the developed world has often influenced its environmental relations. The extreme faith in the quality of goods from developed countries like the United States and the UK often validate the market for foreign-used goods.…”
Section: Hazardous Waste Management In Africamentioning
confidence: 99%